Kajian Teologis tentang Mazmur 23:1-6 dan Penerapannya dalam Pelayanan Gereja Masa Kini - Gulo, Miraniat Hati; Gulo, Agustinus; Sihombing, Herdiana (Jurnal Teologi dan Pelayanan Kerusso, 2024)
Psalm 23:1-6 is one of the most well-known passages in the Christian tradition, portraying the intimate relationship between God as the Shepherd and His people as the sheep. In the context of contemporary church ministry, a deep understanding of these verses is crucial, as they offer theological and practical guidance for the faith community in overcoming various spiritual and emotional challenges. This study aims to explore the theological relevance of Psalm 23 in the context of modern church ministry. The primary objective of this research is to conduct a theological analysis of Psalm 23:1-6 and to explore its application in today's church ministry context. This study also seeks to identify how the principles contained in this Psalm can serve as a foundation for pastoral care, spiritual strengthening, and congregation development in the modern church. The research employs a qualitative approach, using literature review and textual analysis methods. The primary sources used include the Hebrew text of Psalm 23:1-6 and modern translations, while secondary sources comprise various theological literature, Bible commentaries, and writings from related theological experts. This research also utilizes hermeneutical methods to delve deeper into the meaning of the text and its interpretation in various historical and theological contexts. The results indicate that Psalm 23 portrays God as a Shepherd who nourishes, protects, and guides His people, creating a sense of security and trust for those who follow Him. These attributes are relevant to contemporary church ministry, particularly in the context of pastoral care and spiritual support for congregants facing life crises. The findings also suggest that the application of the values contained in Psalm 23 can strengthen church ministry strategies in providing comfort, trust, and hope to its members. This study concludes that Psalm 23 holds strong and practical relevance for modern church ministry, as it offers an ideal depiction of divine care that can be applied in pastoral ministry. The church can use the principles from this Psalm to build trust and hope among congregants, as well as to provide more effective spiritual support in addressing the challenges of modern times.